Essential oils as natural fungicides to control rhizopus stolonifer-induced spoiled of strawberries - Filho, Josemar Gonçalves Oliveira [UNESP]; Silva, Guilherme da Cruz; Egea, Mariana Buranelo; de Azeredo, Henriette Monteiro Cordeiro; Ferreira, Marcos David (AMG Transcend Association, 2021)
Strawberry is a highly desirable fruit with a unique taste and a good source of bioactive compounds beneficial to human health. However, it has a short post-harvest shelf life, mainly due to the soft rot caused by Rhizopus stolonifer. This study aimed to evaluate the antimicrobial properties of essential oils (EOs) of Mentha piperita, Cymbopogon martinii, Cinnamomum camphora, and Mentha spicata using spore germination and micro-well dilution assays, and to test the effects of the vaporphase application of M. spicata and C. martini on the incidence and severity of soft rot in strawberry artificially inoculated with R. stolonifer. In in vitro tests, C. martinii and M. spicata EOs were the most effective, inhibiting more than 95% of the spore germination. Additionally, in the microwell dilution test, these EOs had the lowest minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) (5 and 10 μg/mL, respectively), and for the microwell dilution test, the lowest MIC (5 μg/mL and 10 μg/mL, respectively) and MFC (10 μg/mL for both). High in vivo inhibitory effects of M. spicata and C. martinii EOs were observed at 10% concentration, with 100 and 78% reduction, respectively, in the R. stolonifer-induced spoilage. Our results suggest that C. martinii and M. spicata EOs can be used as efficient natural fungicides and can be an alternative to synthetic fungicides for preserving fresh strawberries from soft rot.
Keywords: Minimal inhibitory concentration; Natural antifungal agent; Plant essential oils; Soft rot